SPEAKING SKILL IN 21ST-CENTURY: STUDENTS’ PERCEPTIONS AND CHALLENGES IN ENGLISH LANGUAGE TEACHING - Leonita, Ni Nyoman Saka Nimas Ajeng; Apriyanti, Ni Putu Ria; Krismayani, Ni Wayan; Joni, Dewa Ayu Ari Wiryadi; Budiarta, I Komang (Premise: Journal of English Education and Applied Linguistics, 2023)
It is crucial to learn a new language, especially English, an international language. Nowadays, having the ability to speak English is an essential ability for students to have. Good speaking skills will help them communicate with each other, speak their minds, pronounce words correctly, and construct sentences in grammatically correct terms. This research aims to analyze the students' perception and challenges of speaking skills in the 21st -century. Twenty-six students were taken randomly from three classes enrolled in the Speaking for Informal Interaction of the English Language Education Study Program, Universitas Mahasaraswati Denpasar. The researchers used open-ended questionnaires and semi-structured interviews and analyzed using the qualitative research approach. Recordings and documents supplemented the instruments. The collected data were transcribed, classified, interpreted, and concluded as the findings of this study. The finding reveals students' perception of the need for English textbooks to support their communicative competencies and some challenges affecting their ability to master speaking skills. Lacking in terms of vocabulary, grammar, pronunciation, self-confidence, lack of knowledge, fear of making mistakes, low motivation, fear of criticism, shyness, and nervousness are some challenges the students face. Based on the students' perceptions and challenges, the lecturers are suggested to develop a textbook that can accommodate the student's needs and challenges. Students need a coursebook to build confidence to speak in public.